Effects of ownership concentration on firm performance: Pakistani evidence - Qaiser Rafique, Yasser; Abdullah, Al Mamun (Emerald Group Publishing Limited, 2015)
Purpose – This paper aims to present an analysis of the association between five categories of concentrated ownership and firm performance in Pakistan. The connection between high ownership concentration and firm performance has attracted much attention, especially in emerging market, yet yielded many inconsistent empirical results. Design/methodology/approach – Karachi Stock Exchange (KSE)-100 Indexed companies listed in KSE from 2007 to 2011 were selected as the sample, and correlation coefficient and regression model were used to inspect the relationship between ownership concentration degree and corporate performance. Findings – It was found that there is no significant association with ownership concentration and accounting-based performance, market-based performance measures and economic profit, in general. Originality/value – The first demonstration that the shareholding proportion of the single largest shareholder is the only variable having positive association with market-based performance measures.